Implementing the theoretical domains framework in occupational safety: Development of the safety behaviour change questionnaire. (April 2021) - Morgan, James I.; Curcuruto, Matteo; Steer, Michael; Bazzoli, Andrea
Highlights: Development and validation of the SBCQ tool based on the TDF. 3 rail worker samples utilised. 3 target safety behaviours - slip/trip hazards, PPE usage, or safe tool storage. 3 stage validation resulted in 26-item questionnaire covering 13 TDF domains. SBCQ can be utilised to guide the design of safety interventions. Abstract: Understanding the factors that either facilitate or hinder the performance of specific safety behaviours is important in developing effective intervention strategies. A questionnaire to identify determinants of safety behaviours for safety–critical workers does not currently exist. This study reports the development and validation of the Safety Behaviour Change Questionnaire (SBCQ) based on the Theoretical Domains Framework (TDF). Following initial questionnaire development, a 3-stage testing procedure was adopted with three independent rail worker samples (totalling 620 participants), with a focus on three separate specific safety behaviours (removing slip/trip hazards, using PPE, safe tool storage). Exploratory factor analysis (EFA) was used for the identification of the underlying structure of the initial set of items. Confirmatory factor analysis (CFA) was undertaken to generate the model of best fit at the calibration and validation stages. The final version of the SBCQ consisted of 13 factors and 26 items. Subsequent analysis of psychometric invariance confirmed the stability of the model factor structure across three distinct research sub-samples. These initial results suggest that the SBCQ demonstrates reliable, stable and valid properties, and that it can be utilised by safety managers and practitioners to guide the design of safety interventions for a range of safety behaviours.